Characterization of a maize root proteinase. - Goodfellow, V J (1993)
The major proteinase in maize (Zea mays) roots behaves as a serine endopeptidase. A possible physiological role of this enzyme could be in the turnover of nitrate reductase (NR) and, as such, it could be of great importance in regulating the assimilation of nitrate. The objective of this research was to elucidate the specificity and uniqueness of maize root proteinase. When bovine serum albumin and an NR purified from Chlorella vulgaris were used as substrates, the maize root proteinase exhibited a preference for cleavages such that the amino acid on the amino side of the scissile bond was alanine. This information was established by microsequence analysis of the N termini of proteolytic fragments, and carboxypeptidase Y analysis of the C termini of proteolytic fragments of substrates hydrolyzed by the proteinase. Cleavage occurred at the sequence Ala/Ala-Ala-Ala-Pro-Glu in Chlorella NR, and at the sequence Ala-Asp-Glu-Ser-His-Ala-Gln in bovine serum albumin. When bovine serum albumin was the substrate, the maize root proteinase yielded a peptide map that is unique relative to those created with the other serine endopeptidases elastase, trypsin, or chymotrypsin. Based on our data, the maize root proteinase appears to cleave peptide bonds at the carboxy side of alanine. Because of its specificity, it should have useful applications in protein chemistry.